南極海インド洋区における海洋生態系の長期的変動解析 ―日豪協共同研究の発展の成果― - 福地, 光男; アンソニー, プレス; 川口, 創; 小達, 恒夫; Fukuchi, Mitsuo; Press, Tony; Kawaguchi, So; Odate, Tsuneo (2010)
Currently, the majority of Antarctic research information is collected from the Southwest Atlantic (Antarctic Peninsula - Weddell Sea region), where there are many Antarctic stations, including long-term ecosystem monitoring sites. Similar ecosystem monitoring sites are lacking in other areas of the Antarctic, although environmental trends and rates of changes differ between regions of the Antarctica. Japanese Antarctic Research Expedition (JARE) has been conducting the long-term routine marine observations since 1965/66 of JARE-7 along the cruise track between Australia and Syowa Station, Antarctica, through the Indian sector of the Antarctic Ocean. However, the timing and location of observation have been almost fixed every year. These routine data is useful to analyze the long-term variability of marine systems, such as physical condition, chemical properties, plankton biomass and productivity as well as air-sea interaction of CO2 exchange. In 2001/2002 summer, the JARE 43rd launched the STAGE program (STudies on Antarctic Ocean & Global Environment), which focuses on time-series continuity of observation based on multi-ships survey under the international framework. On the other hand, the Australian Antarctic marine program has been covering the wide expansion from west to east in the Indian sector and they are also accumulating a wide range of data base on marine ecosystem. During the IPY summers, the intensive survey of CAML (Census of Antarctic Marine Life) was carried out, in particular the CPR (Continuous Plankton Recorder) samplings were carried out on several vessels and the CPR collaboration between Japan and Australia has been continuing before and after the IPY and is developing the multi-national program. Japan and Australia are now bringing both data base together and analyzing to detect/extract any changes in the marine systems. Overview of the current program of Japan-Australia collaboration in analyzing the long-term change of the marine ecosystem in the Indian sector of the Antarctic ...